Eksistensi Radio Saat Ini : Studi Preferensi & Motivasi Khalayak Dalam Mendengarkan Radio - Miranda, Pritta; Yuliati, Reny (Faculty of Communications Science, Dr. Soetomo University, 2020)
Radio is an audio medium used to fulfil the needs the audience's need, both for information and entertainment. Radio provides a variety of information content and a choice of music. Amid technological developments, the presence of many choices of media to access news, entertainment, music, and other information has become a challenge for radio broadcasting. Now people have various choices of media to get information and listen to music. This research aimed to look at the choice of media, especially radio, from the audience and find out what makes radio remains the audience's choice for information, entertainment and listening to music compared to other new media, including the reasons and motivations of audiences to listen to the radio. The results showed that audiences tended to prefer radio over other media because radio offered unique things, for example, the element of 'surprise' in selecting songs that give different sensations. In addition, the presence of radio broadcasters is also considered entertaining and can be a companion to the audience, especially when travelling. These results indicate that radio offers a uniqueness that cannot be found in other media, and the audience is free to choose the media based on their motivations, the greatest of which is listening to the radio for music, entertainment, and information.